ETIKA DALAM ASURANSI KESEHATAN: MENEMUKAN KESEIMBANGAN DAN KEADILAN - Annisya Putri Salsabila; Putri Naira Kusuma; Riswandy Wasir; Cahya Arbitera (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Background: Ethics is an important component of business. In the world of health insurance, ethics are needed to support justice and balance for companies and consumers. Companies are obliged to fulfil consumer rights in full, but there are still many companies that prioritize profit alone by committing fraud. This research is expected to provide in-depth insight into ethical issues and help health insurance companies run their businesses in an ethical and responsible manner. Method: The method used in this research is a systematic review using Google Scholar and PubMed databases over the last 5 years. Result: From the results of the analysis, it was found that ethical violations in health insurance still frequently occur. Fraudulent acts are often carried out by insurance companies, such as falsifying documents and rejecting insurance claims. This is certainly not in accordance with health insurance business ethics and does not uphold consumer justice. Conclusion: From the research conducted, it can be concluded that awareness regarding ethics in the health insurance business is still low. However, there are several solutions that can be implemented, such as increasing cooperation between the government, regulators, and insurance companies. Keywords: Health Insurance, Ethics, Justice, Balance